Religiosity and Romanticism in Mandar's Love Poem Text: Stylistic Analysis - Rasyid, Nirwana; Mahfuddin, Mahfuddin; Fitriana, Irna (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
The purpose of this study was to find the lexical form of religiosity and romanticism contained in the Mandar Sayang-sayang poetry. The type of research used is qualitative research, with qualitative descriptive methods. Sampling was done by using purposive sampling technique. The data collection procedure used a literature review procedure, listening method, note-taking technique, and reflective-introspective. The data analysis model used is an interactive model (interactive model). The results of the study found that the lexical containing the meaning of religiosity was found in the verse at the beginning of the text Sayang-sayang Mandar. Meanwhile, the lexical containing the expression of romanticism is found in almost all stanzas of the Mandar Sayang-Sayang text. The Mandar affectionate poetry is an expression of religiosity and the character of mutual love for fellow Mandar people and for all human beings in the world.